P154 Faecal calprotectin and patient reported disease control of IBD: results from the baseline dataset of the PREdiCCt study. (27th May 2021) - Siakavellas, S; Derikx, L; Derr, L; Williams, L; Plevris, N; Jenkinson, P; Lucaciu, L; Constantine-Cooke, N; Covil, K; Murdoch, L; Jones, G R; Lees, C
Abstract: Background: There is an established disconnect between intestinal inflammation and symptoms in patients with IBD. Faecal calprotectin (FCAL) is an excellent surrogate for mucosal healing and we have good data to support treat to target approaches based on FCAL. However, there is relatively little data analysing how well FCAL correlates with a fuller breakdown of a patient's symptoms. We were interested to explore the impact of ongoing intestinal inflammation as measured by FCAL in patients reported to be in clinical remission. Methods: The PREdiCCt study (https://www.predicct.co.uk ) is the largest prospective study of the causes of IBD flare. 2629 patients in clinical remission were recruited from 48 UK sites and followed for 2 years. 1946 (74%) patients completed the baseline questionnaires. We present here the results of the baseline questionnaire analysis of IBD symptoms (IBD Control questionnaire). Eight of the question items generate a summary score (IBDControl-8) ranging from 0 (worst control) to 16 (best control). This questionnaire also includes a visual analogue scale (VAS) for disease control ranging from 0 (worst control) to 100 (best control). These data were matched to a contemporaneous FCAL measurements, taken at study entry. Results: IBD Control-8 results are available in 1, 919 patients [male=840, CD=985 UC/IBDU=934, age 45.8±15.5 (mean±SD in years)]). Median FCAL values were 46 mcg/g (IQR 20–150) for the overall cohort, 50 mcg/g (IQR 20–156) for CD and 39 mcg/g (IQR 20–143) for UC. UC patients reported better disease control compared to CD patients (p<0.001, for both IBDControl-8 and VAS). CD patients with previous surgery (p=0.031 for IBDControl-8) and perianal disease (p=0.015 and p=0.035, for IBDControl-8 and VAS respectively) reported worse disease control than the rest of the CD patients. Better disease control was reported in males versus female patients (p<0.001 and p=0.003 for IBDControl-8 and VAS respectively). There was a negative correlation between baseline FCAL values and (p<0.001). Patients who reported waking up at night due to their disease had higher FCAL values at baseline [median 60 mcg/g (IQR 20–162) vs 43 mcg/g (IQR 20–144), p=0.013] with the correlation being more prominent in UC (p=0.002). Patients who reported the need to change their treatment had higher FCAL values at baseline [85 mcg/g (IQR 24–336) vs 43 mcg/g (IQR 20–139), mcg/g, median (IQR), p=0.032]. Conclusion: This is the first detailed symptom examination of clinical versus deep remission. We show how residual gut inflammation in patients in clinical remission affects meaningful patient reported outcomes measures including waking at night. UC and male patients reported better disease control compared to CD and female patients.